Understanding herpes zoster vaccine hesitancy and information asymmetry: a qualitative study in China - Wang, Xiaolong; Xing, Yufei; Zhang, Enming; Dai, Zhengyue; Li, Yuan; Shang, Shuhui; Hu, Jiale; Zhang, Xian; Fang, Qiong (Frontiers in Public Health, 2024)
Background Herpes zoster is more prevalent among the elderly due to the age-related immune decline, leading to significant pain and complications. Although vaccination effectively prevents viral infections, vaccine hesitancy remains a major barrier to achieving high vaccination rates.To address this, we conducted a qualitative survey using Vaccine Hesitancy Determinants Matrix and 5C model to understand and improve vaccination rates in this group.Methods Descriptive qualitative research design based on the philosophical underpinnings of naturalistic inquiry and purposive sampling methodology was conducted on adults aged 50 and above, as well as community health workers. Data were collected through semi-structured, in-depth personal interviews. The interview outline was constructed following a comprehensive review of the literature and consideration of the theoretical framework.Seventeen adults over 50 years and four community healthcare workers were included in this study. The study found that information asymmetry in immunization planning was evident at all stages of vaccine supply, dissemination and demand. The main manifestations included limited access to authoritative information, insufficient community awareness of herpes zoster as a route of vaccination, insufficient vocational training, significant gaps in vaccine knowledge, and high levels of complacency among individual residents.Herpes zoster vaccine hesitancy is prevalent among middle-aged and older adults in China due to information asymmetry, vaccine complacency, inadequate community services, and other multiple layers of factors. Public health strategies should aim to reduce cognitive biases and information gaps by disseminating diverse and credible vaccine information through social media, medical institutions, and offline channels to promote higher vaccination rates.